Enterovirus D68 infection among hospitalized children with severe acute respiratory illness in El Salvador and Panama, 2012‐2013. Issue 2 (5th December 2020) - Biggs, Holly M.; Nix, W. Allan; Zhang, Jing; Rogers, Shannon; Clara, Wilfrido; Jara, Jorge H.; Gonzalez, Rosalba; Luciani, Kathia; Brizuela, Yarisa Sujey; Estripeaut, Dora; Castillo, Juan Miguel; De Leon, Tirza; et al.
Abstract: We assessed EV‐D68 epidemiology and phylogenetics among children aged ≤9 years hospitalized with severe acute respiratory illnesses at five sites in Panama and El Salvador during 2012‐2013. Respiratory specimens positive for enterovirus or rhinovirus were tested by real‐time RT‐PCR for EV‐D68, and partial VP1 gene sequences were determined. Of 715 enrolled children, 17 from sites in both countries were EV‐D68‐positive and commonly had a history of asthma or wheezing. Phylogenetically, 15 of 16 sequences fell into Clade B1, and one into Clade A2. The Central American EV‐D68s were closely related genetically to contemporaneous strains from North America, South America, and the Caribbean.